SPBE Santri RSUD Sidoarjo: Inovasi Smart Hospital untuk Pelayanan Kesehatan yang Efektif dan Efisien - Riska Putmala Sari; Imelda Dian Rahmawati (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
This study describes the results of innovations from the Android-based Hospital Santri Application (Hospital Queue SMS) at the Outpatient Installation of the Specialist Polyclinic and the Executive Polyclinic of Sidoarjo Hospital, which is an innovation that is very helpful in managing patient queues. Initially, Sidoarjo Hospital used the SMS Queue program to manage patient queues online. However, since September 2019, this program has changed to the Santri RS (Hospital Queue SMS) application which can be downloaded through the Google Play Store. This application aims to facilitate patient needs related to outpatient queues at Sidoarjo Hospital. Patients can register through the Santri RS application or manually with the same queue number. The Santri RS application is supported by a legal umbrella and SOP (Standard Operating Procedure). This ensures that the implementation of innovation runs well. This research highlights the factors that affect the innovation process, including innovation governance, sources of ideas, innovation culture, capabilities and tools, goals, outcomes, and barriers.